2020
DOI: 10.1155/2020/5867086
|View full text |Cite
|
Sign up to set email alerts
|

The Effects and Safety of Chinese Oral Herbal Paste on Stable Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta‐analysis of Randomized Controlled Trials

Abstract: Background. Chinese oral herbal paste has been widely used in the treatment of chronic obstructive pulmonary disease (COPD). However, the treatment effects of herbal paste were controversial and lack evidence to support its clinical use. This study aims to systematically assess the efficacy and safety of Chinese oral herbal paste for the treatment of stable COPD. Methods. PubMed, Web of Science, CENTRAL, EMBASE, CNKI, VIP, CBM, and WANFANG database in addition to two websites of clinical trial registry were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…TCM has focused on the treatment of COPD for thousands of years [ 60 ]. Large-scale clinical trials have confirmed that TCM has made progress in controlling COPD [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…TCM has focused on the treatment of COPD for thousands of years [ 60 ]. Large-scale clinical trials have confirmed that TCM has made progress in controlling COPD [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory system pathologies benefit from the integration between conventional and CAMs, particularly homeopathy, homotoxicology, phytotherapy, acupuncture, and traditional Chinese medicine. A recent systematic review shows that Chinese oral herbal therapies are effective in reducing exacerbations in chronic obstructive pulmonary diseases [32], and different cases of asthma, in which current evidence does not support the systematic use of CAM in adults and children [33].…”
Section: Discussionmentioning
confidence: 99%
“…It could also reduce the number of AEs, and improve the efficiency of clinical treatment 24 . Another systematic review within 19 RCTs showed that the integration of Chinese medicine ointment and conventional Western medicine treatment could reduce the number of AEs and improve scores of SGRQ and CAT 25 . One more systematic review covering 100 RCTs showed that, on the basis of the conventional Western medicine treatment, giving TCM treatment based on syndrome differentiation combined acupuncture and moxibustion treatment could improve patients’ lung function, reduce the number of AEs, and improve scores of CAT, etc 26 .…”
Section: Clinical Questions and Recommendationsmentioning
confidence: 99%